Fleksibilitas dan Improvisasi dalam Struktur Cak-ing Pakeliran Lakon Kalimasada Versi Ki Timbul Hadiprayitno - Bayu Aji Nugroho (Institut Seni Indonesia Yogyakarta, 2019)
This paper aims to track cak-ing pakeliran of the Ki Timbul Hadiprayitno version of Lakon Kalimasada. The tracking was used to see Ki Timbul Hadiprayitno’s openness towards today’s development of cak-ing pakeliran. In other words, this paper aims to trace the flexibility of Ki Timbul Hadiprayitno’s attitude as a puppeteer who was in jaman kelakoné. The concept of cak-ing pakeliran Mudjanattistomo et al. (1977) used as a theoretical basis. From the results of the analysis of the cak-ing pakeliran in the Lakon Kalimasada, it was found that the conclusion of Ki Timbul Hadiprayitno gave its own color in the pack of Yogyakarta style pakeliran. He followed the development of the era without damaging the existing cak-ing rules of the Yogyakarta style Pakeliran. It can be said of Ki Timbul Hadiprayitno, who was known as the mastermind who firmly maintained the Yogyakarta style puppetry, it turned out that in his career development was open to changes and developments.Tulisan ini bertujuan melacak cak-ing pakeliran Lakon Kalimasada versi Ki Timbul Hadiprayitno. Pelacakan tersebut digunakan untuk melihat keterbukaan Ki Timbul Hadiprayitno terhadap perkembangan cak-ing pakeliran jaman ini. Dengan kata lain tulisan ini bertujuan melacak kelenturan sikap Ki Timbul Hadiprayitno sebagai seorang dalang yang anut jaman kelakoné. Konsep struktur cak-ing pakeliran Mudjanattistomo dkk. (1977) digunakan sebagai landasan teori. Dari hasil analisis terhadap cak-ing pakeliran Lakon Kalimasada didapatkan kesimpulan Ki Timbul Hadiprayitno memberikan warna tersendiri dalam kemasan pakeliran gaya Yogyakarta. Ia mengikuti perkembangan jaman tanpa merusak kaidah caking pakeliran gaya Yogyakarta yang sudah ada. Dapat dikatakan Ki Timbul Hadiprayitno, yang dikenal sebagai dalang yang teguh mempertahankan pedalangan gaya Yogyakarta, ternyata dalam perkembangan kariernya terbuka terhadap perubahan dan perkembanganjaman.